Strength training alters the tissue fatty acids profile and slightly improves the thermogenic pathway in the adipose tissue of obese mice - de Melo, Diego Gomes; Anaruma, Chadi Pellegrini [UNESP]; da Cruz Rodrigues, Kellen Cristina; Pereira, Rodrigo Martins; de Campos, Thais Dantis Pereira; Canciglieri, Raphael Santos; Ramos, Camila Oliveira; Cintra, Dennys Esper; Ropelle, Eduardo Rochete; da Silva, Adelino Sanchez Ramos; Pauli, José Rodrigo; Moura, Leandro Pereira de (Springer Nature, 2022)
Obesity is a disease characterized by the exacerbated increase of adipose tissue. A possible way to decrease the harmful effects of excessive adipose tissue is to increase the thermogenesis process, to the greater energy expenditure generated by the increase in heat in the body. In adipose tissue, the thermogenesis process is the result of an increase in mitochondrial work, having as substrate H+ ions, and which is related to the increased activity of UCP1. Evidence shows that stress is responsible for increasing the greater induction of UCP1 expression via β-adrenergic receptors. It is known that physical exercise is an important implement for sympathetic stimulation promoting communication between norepinephrine/epinephrine with membrane receptors. Thus, the present study investigates the influence of short-term strength training (STST) on fatty acid composition, lipolysis, lipogenesis, and browning processes in the subcutaneous adipose tissue (sWAT) of obese mice. For this, Swiss mice were divided into three groups: lean control, obesity sedentary, and obese strength training (OBexT). Obese animals were fed a high-fat diet for 14 weeks. Trained obese animals were submitted to 7 days of strength exercise. It was demonstrated that STST sessions were able to reduce fasting glycemia. In the sWAT, the STST was able to decrease the levels of the long-chain fatty acids profile, saturated fatty acid, and palmitic fatty acid (C16:0). Moreover, it was showed that STST did not increase protein levels responsible for lipolysis, the ATGL, ABHD5, pPLIN1, and pHSL. On the other hand, the exercise protocol decreased the expression of the lipogenic enzyme SCD1. Finally, our study demonstrated that the STST increased browning process-related genes such as PGC-1α, PRDM16, and UCP1 in the sWAT. Interestingly, all these biomolecular mechanisms have been observed independently of changes in body weight. Therefore, it is concluded that short-term strength exercise can be an effective strategy to initiate morphological changes in sWAT.